Provision of end-of-life care in primary care: a survey of issues and outcomes in the Australian context. Issue 1 (19th January 2022) - Ding, Jinfeng; Johnson, Claire E; Saunders, Christobel; Licqurish, Sharon; Chua, David; Mitchell, Geoffrey; Cook, Angus
Abstract : Objectives: To describe general practitioners' (GPs) involvement in end-of-life care, continuity and outcomes of care, and reported management challenges in the Australian context. Methods: Sixty-three GPs across three Australian states participated in a follow-up survey to report on care provided for decedents in the last year life using a clinic-based data collection process. The study was conducted between September 2018 and August 2019. Results: Approximately one-third of GPs had received formal palliative care training. Practitioners considered themselves as either the primary care coordinator (53.2% of reported patients) or part of the management team (40.4% of reported patients) in the final year of care. In the last week of life, patients frequently experienced reduced appetite (80.6%), fatigue (77.9%) and psychological problems (44.9%), with GPs reporting that the alleviation of these symptoms were less than optimal. Practitioners were highly involved in end-of-life care (eg, home visits, consultations via telephone and family meetings), and perceived higher levels of satisfaction with communication with palliative care services than other external services. For one-third of patients, GPs reported that the last year of care could potentially have been improved. Conclusion: There are continuing needs for integration of palliative care training into medical education and reforms of healthcare systems to further support GPs' involvement in end-of-life care. Further, more extensive collection of clinical data is needed to evaluate and support primary care management of end-of-life patients in general practice.